2014
DOI: 10.1111/ane.12236
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted lesions in acute ischaemic stroke patients with migraine

Abstract: Objectives -There is increasing knowledge about an association between migraine and ischaemic stroke. Cortical spreading depression (CSD) is the probable biological substrate of migrainous aura. To investigate the influence of CSD on the apparent stroke -migraine association, we hypothesized that magnetic resonance (MR) diffusion weighted images of acute ischaemic stroke patients would reveal an association between small cortical infarctions and migraine. Methods -We included all patients admitted to the Berge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
9
1
1
Order By: Relevance
“…Actually, only two previous analyses have attempted to provide information on the association between migraine and lesion volume from acute cerebral ischemia in humans. The first is a retrospective analysis of the Norwegian Stroke Research (NORSTROKE) registry [28], which suggested that, as opposed to what observed in our study, migraine may be associated with smaller volume of acute infarcts. The second is a single-center North American study conducted on a relatively small group of acute ischemic stroke patients showing, as suggested from the present analysis, an increased lesion volume among migraineurs with aura [29].…”
Section: Discussioncontrasting
confidence: 64%
“…Actually, only two previous analyses have attempted to provide information on the association between migraine and lesion volume from acute cerebral ischemia in humans. The first is a retrospective analysis of the Norwegian Stroke Research (NORSTROKE) registry [28], which suggested that, as opposed to what observed in our study, migraine may be associated with smaller volume of acute infarcts. The second is a single-center North American study conducted on a relatively small group of acute ischemic stroke patients showing, as suggested from the present analysis, an increased lesion volume among migraineurs with aura [29].…”
Section: Discussioncontrasting
confidence: 64%
“…Migraineurs among stroke patients were younger and more often females, and a higher proportion of infarcts was due to cardio‐embolism in migraineurs compared to non‐migraineurs. Migraine was associated with small cortical infarctions, suggesting an increased viability threshold with a high risk of infarction in response to small ischemic events in migraine‐susceptible brains . Other studies further support the concept that cerebral hyperexcitability may increase vulnerability to cerebral ischemia.…”
Section: Cerebral Hyperexcitability As a Link Between Migraine And Stmentioning
confidence: 75%
“…However, since treatment according to the guidelines is performed and the governmental medical insurance for the whole nation covers all people in Japan, a treatment bias is not very much likely. Embolism could lead a poor outcome without hyperlipidemia [ 22 , 23 ]. However, influence of embolism should be predominantly on CI.…”
Section: Discussionmentioning
confidence: 99%